Influence of Direct Current–Voltage Accompanied by Charge Flow on CO2 Hydrate Formation - Zhao, Qi; Xia, Zhi-Ming; Xu, Chun-Gang; Chen, Zhao-Yang; Li, Xiao-Sen (Frontiers in Energy Research, 2021)
The capture and storage of CO2 is urgent and crucial to achieve the carbon neutrality goal. Hydrate-based carbon dioxide (CO2) capture technology is one of the promising technologies for capturing and storing CO2. This work studied the nucleation and growth of CO2 hydrate provoked by direct current-voltage accompanied by charge flow with the agitation of 450 rpm at initial pressures of 3.5 MPa and temperature of 274.15 K. The results show physical bubble behavior and electrochemistry mechanisms could influence CO2 hydrate formation process in the application of a voltage. The induction time and semi-completion time of CO2 hydrate formation was decreased by 51% and 27.8% in the presence of 15 V respectively. However, more product of electrolysis, Joule heat and ions, could inhibit the CO2 hydrate formation process in the application of a high voltage (60V). Additionally, high voltage (60V) could change the morphology characteristics of CO2 hydrate from gel-like to whisker-like. This study provides valuable information on the formation of CO2 hydrate under the action of charge flow.